Sociocultural adaptation, translation and pre-testing of the Kannada version of Vanderbilt Head and Neck Symptom Survey 2.0 - Naina Johnson; Janet Jaison Varghese; Krishna Sharan; Venkataraja U. Aithal; Barbara Murphy (SpringerOpen, 2022)
Abstract Background Head and neck cancer (HNC) patients often undergo radiation therapy as part of their treatment. However, radiation therapy can have many side effects, including oral toxicities. Evaluating these toxicities is often considered a challenging task for practicing clinicians due to the lack of assessment tools. The objective of this study is to culturally adapt, translate and validate the Vanderbilt Head and Neck Symptom Survey (VHNSS), an instrument designed to assess oral toxicities and changes in oral functioning in HNC patients receiving radiation therapy. Methods The VHNSS 2.0 was first culturally adapted and translated, following which 36 HNC patients undergoing radiation therapy were identified through the incidental sampling method. The translated version of VHNSS 2.0 was then administered to these patients. Internal consistency was assessed using Cronbach's alpha and Mc Donald's Omega. Test-retest reliability was also analyzed. Results Items of the translated version of VHNSS 2.0 showed good content validity. The omega values yielded higher reliability coefficients than the Cronbach's alpha coefficient. Test-retest reliability was found to be 0.8, indicating good reliability. Conclusions Results of this study suggest that the translated Kannada version of the VHNSS 2.0 is linguistically equivalent to the original version. Hence, this tool can be considered a valid and reliable patient-reported tool to evaluate oral symptomatology in HNC patients speaking the Kannada language.